In situ reforming of lignite pyrolysis volatiles for enriching light aromatics over Ga substituted HZSM-5. (2nd February 2022) - Yang, Zhen; Cao, Jing-Pei; Zhu, Chen; Liu, Tian-Long; Feng, Xiao-Bo; Zhao, Xiao-Yan; Bai, Hong-Cun
Graphical abstract: Highlights: Hierarchical Ga/Al HZSM-5 exhibits high BTEXN yield at 600 °C. Ga and HZSM-5 presented a strong synergy during the formation of aromatics. Ga/Al HZSM-5 keep high stability during 6th cycle reactions. Multifunctional catalysts promote the formation of H2 by dehydrogenation. Abstract: HZSM-5 was hydrothermally synthesized by Ga substitution to regulate the texture properties for light aromatics such as benzene, toluene, ethylbenzene, xylenes and naphthalene (BTEXN) during the lignite volatiles catalytic upgrading process. High BTEXN yield was obtained over xGa/H5(A) (added NaOH in crystallization) and the value increased with raising the amount of Ga incorporation when the Ga content was<1.26 g. 1.26 Ga/H5(A) (1.26 g Ga(NO3 )3 ) displayed the highest yield of BTEXN (29.3 mg/g-daf coal) since Ga species and acidic protons promoted the aromatization process. However, excessive Ga brought a negative effect on the production of aromatics due to the weakened synergistic effect between Ga species and acid sites of H5. Additionally, 1.26 Ga/H5(A) with the interconnected meso -micropores and moderate acidity distribution exhibited excellent reaction stability during the 6 cycle experiments. xGa/H5(A) provided a potential prospect for enhancing the BTEXN formation during catalytic upgrading of lignite pyrolysis volatiles.